Meeting report: The Systemic Lupus International Collaborating Clinics (SLICC) World Lupus Seminar on Africa - Rosalind Ramsey-Goldman; John A Reynolds; Manuel Francisco Ugarte-Gil; Olufemi Adelowo; Omondi Oyoo; Dzifa Dey; Ashira Blazer; Alexandra Legge; Eunice Omondi (Lupus Science and Medicine)
The Systemic Lupus International Collaborating Clinics (SLICC) is an international research group dedicated to promoting collaboration among scientific investigators in the study of systemic lupus erythematosus (SLE). Currently, most SLICC members are based in North America and Europe, with limited representation from other regions. SLICC recognises the importance of expanding its global collaborations and representation to ensure that its research accurately reflects the global burden of SLE and provides equal benefit to all patients with SLE worldwide. Given that SLICC currently lacks representation from the African continent, an opportunity was identified to convene a meeting bringing together lupus physicians with experience providing clinical care and conducting lupus research in Africa, along with members of the SLICC group. The purpose of the meeting was to share information regarding SLE in Africa, to discuss recent innovations and current challenges in the region and to explore future collaborations between SLICC members and colleagues in Africa in the areas of SLE clinical care, research and education. This meeting report highlights information presented during the seminar as well as a discussion of next steps moving forward.